Трансакційні витрати: методико-обліковий аспект - Руда, Т. П.; Ruda, T. P. (Видавництво Львівської політехніки, 2017)
У статті розглянуто сучасні погляди науковців щодо економічної сутності трансакційних витрат. Розкрито сутнісне значення категорії трансакційні витрати діяльності суб’єктів господарювання та запропоноване власне визначення цього поняття. Висвітлено класифікацію трансакційних витрат, види трансакційних витрат та передумови виникнення, що в подальшому забезпечать можливість контролю виник- нення трансакційних витрат та сприятиме їх зниженню і підвищенню ефективності діяльності суб’єктів господарювання.

The article examines applicable scientific views on the economic essence of the transaction costs. The essential meaning of the category transaction costs of business entities is revealed and own definition of the term is proposed. The classification of transaction costs, types of transaction costs and factors of their formation that in the future will provide the ability to control the formation of transaction costs and contribute to their reduction, as well as increase the efficiency of business entities are concidered. From the analysis of representations of transaction costs at various stages of the transaction cost theory it may be concluded that the definition of the researched type of costs depends, firstly; on the, characteristics which the authors concentrate their attention on, describing the economic nature of the transaction costs, secondly, on the amount of costs referred to the transaction category by the authors, and thirdly, on the focus of research on the needs of the theory or practice. The scientifically substantiated typology plays an important role in the research of transaction costs. During the research of transaction costs a wide range of their classifications is expanded. In general, this kind of accumulation of knowledge about the transaction costs is positive, but also leads to chaos in understanding and approach to these costs. One of the most important features of transaction costs is that they allow for significant economies of scope, namely, as transaction volume in the sector increases the costs attributable to a contract reduce. The activity of the market mechanism induces the transaction costs, which increase with the complexity of the interchange circuit, and these costs can be reduced by creating regulatory organizations or mechanisms. According to the research results of scientific sources it is believed that in terms of an aspect of transaction costs are the costs incurred in the process of interaction among entities on the exchange of material assets, activities, as well as the rights and obligations based on the relevant agreements. The proposed definition of transaction costs of business entities is the result of generalization of existing definitions of transaction costs with specification of their formation conditions, providing identification of transaction costs, as well as the total amount of costs of business entities.
Transaction costs: methodological and accounting aspect
Keywords: трансакційні витрати; суб’єкти господарювання; управління; матеріальні активи; собівартість продукції; прибуток підприємства; transaction costs; business entities; management; material assets; production costs; profits of the company; 657.62; 658.29